APRESIASI TERHADAP BATIK MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS SARJANAWIYATA TAMANSISWA YOGYAKARTA - Endang Wani Karyaningsih (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2016)
"> The objective of this research is to describethe students’ appreciation toward batik whichincludes love for batik, knowledge variety of batik, an understanding of batik philosophy, a desire to learn batik, and awareness to wear batik.The research question is how do students at theTeacher Training and Education Faculty of Universitas Sarjanawiyata Tamansiswa appreciatebatik? This research includes a descriptive quantitative research. The number of respondents was119 selected by using a proportional randomsampling technique. The data were revealed byusing a questionnaire. The data analysis useddescriptive quantitative calculations to gainmean, median, mode and standard deviation values. From the calculations, the average value ofbatik appreciation was 59 (an average category).The average value of each indicator consisted of15.9 for the love of batik (an average category);9.1 for knowledge variety of batik (an averagecategory); 10.7 for an understanding of batikphilosophy (a low category); 14.8 for a desire tolearn batik (an average category); and 9.5 forawareness to wear batik (an average category).From these results it is suggested that studentsgain knowledge about batik by reading books inthe future, so they impart knowledge about batikas part of the Indonesian culture that has beenrecognized by UNESCO